1977
DOI: 10.1093/jnci/58.4.923
|View full text |Cite
|
Sign up to set email alerts
|

Reversal by Vitamin A Analogues (Retinoids) of Hyperplasia Induced by N-Methyl-N′-nitro-N-nitrosoguanidine in Mouse Prostate Organ Cultures2

Abstract: The antihyperplastic activity of beta-retinoic acid (RA) and nine synthetic analogues (retinoids) was examined in organ cultures of mouse prostate made hyperplastic by treatment with N-methyl-N'-nitro-N-nitrosoguanidine (MNNG). After 8 or 10 days, when most explants developed hyperplasia, the carcinogen was withdrawn and explants were incubated in control medium and medium containing different concentrations of a retinoid. The antimitotic activity of retinoids was compared with that of RA. Different retinoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…In addition to inhibiting cancer development, retinoids also have antiproliferative and differentiation-inducing activity in cultured cell lines. Retinoids have effectively inhibited proliferation of tumor cells in culture and have reversed the anaplastic or hyperplastic changes induced in mouse prostatic epithelial cells by carcinogenic hydrocarbons [14]. Lasnitzki [20,21] and Lasnitzki and Goodman [22] showed that premalignant changes (squamous metaplasia and hyperplasia) of mouse prostate glands treated with 3-methylcholanthrene could be reversed by retinoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inhibiting cancer development, retinoids also have antiproliferative and differentiation-inducing activity in cultured cell lines. Retinoids have effectively inhibited proliferation of tumor cells in culture and have reversed the anaplastic or hyperplastic changes induced in mouse prostatic epithelial cells by carcinogenic hydrocarbons [14]. Lasnitzki [20,21] and Lasnitzki and Goodman [22] showed that premalignant changes (squamous metaplasia and hyperplasia) of mouse prostate glands treated with 3-methylcholanthrene could be reversed by retinoids.…”
Section: Discussionmentioning
confidence: 99%
“…Lotan and Nicolson [12] studied the antiproliferative activity of retinoic acid and retinyl acetate in 31 different cell lines, and found growth to be inhibited in >60% of them. In the prostate, Chopra and Wilkoff [14] effectively inhibited proliferation of tumor cells in culture, and reversed the anaplastic or hyperplastic changes induced in mouse prostatic epithelial cells by carcinogenic hydrocarbons. Although the antitumor effects of retinoids have been tested in different cell cultures, their effect on prostatic ductal development and branching has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Aber auch Drtisenepithelien und das Epithel des Urogenital-und Verdauungstraktes scheinen Vitamin A-sensibel zu sein: so erwiesen sich Mammacarcinome [22], Tumoren der Harnblase [29] und der Prostata [6] als Vitamin A-empfindlich.…”
Section: Tumor-inhibierende Effekte Des Vitamin a Wurden Yon Verschieunclassified
“…ATRA is being used in differentiation therapy of cancer, in cancer chemoprevention and for the treatment of acne [35]. Recently, ATRA has proven useful in cancer chemotherapy [6–8]. One of the most impressive effects of ATRA is on acute promyelocytic leukaemia.…”
Section: Introductionmentioning
confidence: 99%